Online gaming: A data-driven regulatory framework - Aishvarya et al (Economic and Political Weekly)
Online gaming and online fantasy sports platforms have experienced tremendous growth and popularity as a result of increasing internet penetration, affordable smartphones, and COVID-19-linked social isolation. They have been the subject of numerous legal disputes because of concerns over excessive participation of youngsters, leading to addiction, financial difficulties, and gambling. Many Indian states recently amended their online gaming laws to introduce a blanket ban on online gaming, which was met with intense pushback and criticism from both the judiciary and industry. The need for a data-driven regulatory framework that classifies online games based on their nature and statistically evaluates the dominance of skill and chance in a gaming set-up are highlighted in this paper. Taking OFS as a use case, these statistical tests are described and factors are identified that can help in designing skill-dominant platforms. Drawing on lessons from other countries, certain initiatives are suggested to address societal concerns such as addiction, protection of minors, and responsible advertising.- Reproduced